Manganese(II), Cobalt(II), Nickel(II), Copper(II) and Zinc(II) Complexes of N-(o-Hydroxy Methyl Substituted Benzyl) Glycines - Ballabh Melkani, Kirti; Sharma, Reeta; Chandra, Madhup (Asian Journal of Chemistry, 2010)
1 : 1 Mn(II), Co(II) , Ni(II), Cu(II) and Zn(II) complexes of N-(o-hydroxy methyl substituted benzyl) glycines have been isolated from 50% (v/v) aqueous dimethylsulphoxide medium and characterized by elemental analysis and spectral measurements.